Interference aware cluster-based joint channel assignment scheme in multi-channel multi-radio wireless mesh networks - Ali, Saqib (2013)
Wireless Mesh Networks (WMNs) are emerging as a promising solution for robust and ubiquitous broadband Internet access in both urban and rural areas. WMNs extend the coverage and capacity of traditionalWi-Fi islands through multi-hop,multichannel and multi-radio wireless connectivity. The foremost challenge, encountered in deploying a WMN, is the interference present between the co-located links, which limits the throughput of the network. Thus, the objective of this research is to improve the throughput, fairness and channel utilization of WMNs by mitigating the interference using optimized spatial re-usability of joint channels available in the 2.4 GHz Industrial, Scientific, and Medical (ISM) band. Interference is quantified depending on the relative location of the interfering links. Further, the Interference aware Non-Overlapping Channel assignment (I-NOC) model is developed to mitigate the interference by utilizing optimized spectral re-usability of Non-Overlapping Channels (NOCs). NOCs are limited in number. Therefore, I-NOC model is extended by using joint channels available in the free spectrum, and termed as Interference aware Joint Channel Assignment (I-JCA) model. Normally, joint channel assignment is considered harmful due to adjacent channel interference. However, by systematic optimization, the I-JCA model has utilized the spectral re-usability of joint channels. I-JCA model cannot be solved at the time of network initialization because it requires prior knowledge of the geometric locations of the nodes. Thus, Interference aware Cluster-based Joint Channel Assignment Scheme (I-CJCAS) is developed. I-CJCAS partitions the network topology into tangential non-overlapping clusters, with each cluster consisting of intra- and inter-cluster links. I-CJCAS mitigates the interference effect of a cluster’s intra-cluster links by assigning a distinct common channel within its interference domain. On the other hand, the inter-cluster links are assigned to a channel based on the transmitter of the inter-cluster link. I-CJCAS is benchmarked with Hyacinth, Breadth-First Search Channel Assignment (BFS-CA) and Cluster- Based Channel Assignment Scheme (CCAS) in terms of throughput, fairness, channel utilization, and impact of traffic load in single-hop and multi-hop flows. Results show that I-CJCAS has outperformed the benchmark schemes at least by a factor of 15 percent. As a part of future work, I-CJCAS can be extended to incorporate dynamic traffic load, topology control, and external interference from co-located wireless network deployments.